Regeneration versus demolition. Strategies, actions and local practices on Yongqing Fang Site - Edoardo Bruno; Francesco Carota (Agathón)
The quick economic and urban growth of China has deeply changed its urban image, promoting both new types of settlement and the demolition of large surfaces to make room for new real estate interventions. In the variable physical and regulatory context of the cities of contemporary China, the development of some pilot projects becomes an opportunity to experiment with innovative regeneration practices of existing urban fabrics. The analysis of the Yongqing Fang case study, located in the old town of the megacity Guangzhou, shows the need to change the practice of the regeneration project within a detailed and negotiated co-operation between public and private, to favour the demand towards the historical Assets of the city. Moreover, the case study allows to implement an analysis model to recover cultural heritage within a holistic and procedural perspective, where the project becomes a tool for negotiation, selective space transformation, urban renovation and social inclusion.